Prediction of Natural Gas Compressibility Factor in a Single-Phase Gas Reservoir: A Comparative Study - Bello, M. N.; Musa, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
Natural gas compressibility factor plays important roles in pipeline design, reserve estimation and gas metering. The aim of this study is to presents the most accurate and reliable method of computing gas compressibility factor in a single-phase gas reservoir at various reservoir pressures. In this study, the gas compositions and the specific gravity of the respective gas compounds were retrieved from literatures. This specific gravity determine the pseudo critical and the pseudo reduced properties (temperature and pressure) of the respective gas compounds being studied. The predicted methods studied are Papay correlation, Hall-Yarborough equation of state (EOS), viral EOS, Beggs and Brill and Dranchuk-Abu-Kassem correlation. The methods are expressed as functions of the pseudo-reduced temperature and pressure, thereby predicting the compressibility factor of the predicted methods. The accuracy and the performance of the methods were tested by comparing the results obtained from the methods studied with experimental z-factor values obtained from the literatures. The experimental z-factor values were set as standard for the predicted methods studied. Six (6) statistical parameters and various charts (line and column charts) were used to attest the effectiveness and the precision of the methods. The statistical tools are average absolute error (AAE), average absolute relative error (AARE), root mean square error (RMSE), residual sum of square (RSS), mean square error (MSE) and coefficient of determination (R2). The results of the study shows that, the Papay correlation has the highest coefficient of regression, R2= 92%, rated as the most accurate, reliable and best method. The Hall-Yarborough equation of state has R2 of 86%. The Viral equation of state has R2 of 83%. The Beggs and Brill correlation has R2 of 42%. The Dranchuk-Abu-Kassem correlation has R2 of 10.5%. The Beggs and Brills correlation method is not suitable for application, if the pseudo-reduced pressure is less than 0.92. The Dranchuk-Abu-Kassem correlation is only applicable, if the pseudo-reduced properties are within the range of 0.2<Ppr<15, 1.0<Tpr<3.0. The Hall-Yarborough equation of state cannot be used if the pseudo-reduced temperature is less than one.